Sosialisasi Pengendalian Pencemaran Lingkungan Hidup di SMP Negeri 2 Kecamatan Siak Hulu - Sisca Vaulina (Universitas Pahlawan Tuanku Tambusai, 2023)
Public Senior High School 2 Siak Hulu is an educational unit level in Pangkalan Baru, Siak Hulu District, Kampar Regency, Riau. In its development, has various problems, i.e., garbage scattered students the school environment, several semesters do not carry out face-to-face learning. Student awareness about importance of living healthy life and keeping the environment clean is very minimal, therefore it needs socialized about controlling environmental pollution. Community Service Team (PKM) is interested in providing legal counseling on environmental pollution control at this school. This activity focuses on procuring the implementation of environmental pollution control socialization. The purpose of this activity is to provide: (1) legal counseling on environmental pollution control; (2) knowledge about the impact of environmental damage due to scattered waste. The results of the activity, new knowledge for students regarding environmental pollution and environmental destruction are different things. Need awareness of students to protect and preserve the environment.